PENGEMBANGAN INSTRUMEN EVALUASI DENGAN TEKNIK SIMULASI SEBAGAI ASESMEN ALTERNATIF DALAM PEMBELAJARAN FISIKA MATERI MEKANIKA FLUIDA SMA KELAS XI - Murtono .; Evi Miskiyah (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
This research aims to generate and determine the quality assessment of simulation, determine the validity, reliability, and reusability of the instruments, as well as knowing accommodated in problem-solving ability with simulation techniques as perceived by students . Development of research procedures adapted to the model of the development of Four - D finite covering Define, Design, and Develop. By presenting a matter physics through physical phenomena simulated by the computer, as perceived by the students through the assessment they can leverage capabilities that include verbal ability, visual - spatial, logical - mathematical, body - kinesthetic, interpersonal, intrapersonal and natural in problem-solving. The response of students to the application of simulation assessment is positive. While the quality of the products developed assessment simulations is very good with a score of 3.75 according to the details of assessment experts & mater, according to media expert 3.83, and 3.42 according to physics teacher and in accordance with the data analysis, simulation assessment meets the criteria as a matter of valid, reliable, and usabel.